A modelagem matemática no estudo da cinética de degradação de polímeros biodegradáveis - Pontarolo, Edimar Lia (2020)
Biodegradable polymers, such as PCL and PBAT, have received special attention because they are easily degraded, their wide possibility of industrial and technological use, and mainly, because it is a viable way to minimize the effects of high disposal solid waste. The present work consisted in the preparation and characterization of the poly (butylene adipate co-terephthalate) - PBAT and (polycaprolactone) - PCL films and their blends, in addition to the incorporation of iron oxide nanoparticles, as well as the study of biodegradation in composted soil for a period up to 120 days. After removal of the samples from soil, characterizations were carried out by Fourier transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA), differential scanning calorimetry (DSC), X-ray diffraction (XRD), angle contact measurement and scanning electr on microscopy (SEM), which demonstrated the significant occurrence of biodegradation, mainly at PBAT/PCL blends. In FTIR, the analysis of the bands showed that the biodegradation process occurs mainly from the hydrolytic fission of the ester groups and this process occurs more effectively in the PBAT/PCL blend than in the pure PBAT. The DSC and DRX curves revealed a relative increase in crystallinity, since the amorphous part of the polymer is the first to be degraded during the process. The measurement of the contact angle showed that the degradation favors the increase of roughness and the formation of polar species on the polymer’s surfaces. Finally, the studies of mass loss and the mathematical profile of the degradation kinetics showed that the process occurs more effectively in the blends, as well as suggesting that the process occurs preferably through a second order mechanism, presenting as a predominant factor the surface erosion that occurs more favorably in the PBAT/PCL blend, due to the greater susceptibility of the PCL to biodegradation.